An Effectual Approach to International Entrepreneurship: Overlaps, Challenges, and Provocative Possibilities. (28th November 2013) - Sarasvathy, Saras; Kumar, K.; York, Jeffrey G.; Bhagavatula, Suresh
<x xml:space="preserve">Abstract</x> In this paper, we outline several interesting observations about international entrepreneurship (IE) research through the theoretical lens of effectuation. In doing so, we show how an effectual approach can help resolve four central conflicts and knowledge gaps identified in two recent comprehensive reviews of IE. We then present an illustrative case study from India that provides an intriguing comparison with the most recent modification of the Uppsala model to integrate with effectuation theory. Finally, we offer four provocative possibilities for future research at the intersection of IE and effectuation research.